The Existence of Dhikr Rateb Siribee in the Naqshbandiyya Tariqah Congregation at Raudhatul Hikmah Al-Waliyyah Dayah, Pango Raya, Banda Aceh - Marfuah, Sururin; Harahap, Mardian Idris (UNIVERSITAS PAKUAN, 2020)
As servants of Allah, humans are required to always remember and mention Allah in order to get the ultimate peace. Zikr is remembering Allah by appreciating His presence, His Holiness, His Praiseworthiness and His Greatness. The focus of the researcher's study is, how is the existence of zikr rateb seribee in the Naqsabandiyah congregation? and whether this zikr rateb seribee can instill Sufi values in the Naqsabandiyah congregation. The method used is qualitative research that uses descriptive-analytical data analysis techniques, namely analyzing the data obtained by conducting interviews, observations and documentation, then through the approach of tasawuf akhlaqi. The purpose is to find out the existence and Sufi values of rateb seribee dhikr in the congregation of Tarekat Naqsabandiyah. Based on the results of the research, zikr rateb seribe is one of the activities or practices of Sufism in the Indonesian Assembly for the Study of Tauhid Tasawuf or known as MPTT-I. The existence of this zikr rateb seribee has developed from year to year until this zikr reaches abroad, the followers of this zikr rateb seribee have tens and even thousands of worshipers who follow it. This dhikr is a recommendation from religion, the congregation of the naqsabandiyah order who performs this dhikr has a kesufian value embedded in them, namely strengthening the relationship, the tongue is always awake from dirty speech and hurting others, and the mind becomes more positive.